Literatura negro-brasileira contemporânea: uma proposta pedagógica com círculos de leitura literária - Urbano, Fransuilza Almeida (2024)
Literature brings with it a human framework as broad as the ways of narrating and creating the literary text itself, hence its relevance throughout the student's academic training, especially in Basic Education, a period in which the reader is in the formative process. The present work aims to be a theoretical and pedagogical contribution to Black Brazilian Literature, since there is still little representation of black writers in school curriculum and teaching materials in Basic Education, even after twenty years of the approved law no. 10,639/03. The purpose of the research is based on reflection and debates promoted by the literary reading of writings of Brazilian blackness, promote self-esteem, a sense of belonging and black identity of Afro-Brazilian students, as well as contributing to racial literacy and anti-racist education for all students involved in the learning process. This research has as theoretical contribution the relevance of the universality of literary work for the development of the student as a whole, the paper is supported by the theories of Candido (1988), Petit (2010), Dalvi (2018), Rouxel (2013), Zilberman (2012), Cosson (2020). To support black-Brazilian literature and ethnic-racial education, we highlight the theoretical assumptions of Cuti (2010), Diogo (2020), Dalcasgnè (2019), Duarte (2014), Gomes (2012), among others, who contributed in reflecting and discussing to expand the space of blackBrazilian literature in basic education as a way of incorporating black culture, history and literature into an egalitarian space in the formation of the country. As a methodology we will use the basic sequence of the Reading Circle, by Cosson (2021). We believe that this research and didactic prototype can provide opportunities for anti-racist and identity-based literary reading so that all students can feel represented in the school space, as well as value the difference in the ways of being, acting and thinking.